INVENTARISASI JENIS DAN RESEP KUE-KUE TRADISIONAL DI KABUPATEN PASAMAN BARAT - Rahmadona, Tiwi; Yulastri, Asmar; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
The purpose of this study was to 1) menginvetaris types of traditional cakes 2) make inventory based on traditional cake recipes that exist in West Pasaman 3) describes the functions of traditional cakes in West Pasaman. This type of research is qualitative research. Data collection techniques by observation, interviews, and documentation. Analysis of field data which includes reduction, display, conclusion and verification. The results showed that (1) the type of cake traditionally found in West Pasaman is two types of traditional cakes of dry and wet tardisional cake. (2) traditional cakes recipe is: there are 15 kinds of traditional pastries and 38 kinds of traditional wet cake. (3) the function of traditional pastries in West Pasaman Kabuapaten is as cakes that were served during traditional events, Eid, souvenirs, and snacks daily. Keywords: Inventory, Traditional Cakes.